2018
DOI: 10.1097/ogx.0000000000000608
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Screening With Primary Cervical HPV Testing vs Cytology Testing on High-grade Cervical Intraepithelial Neoplasia at 48 Months: The HPV FOCAL Randomized Clinical Trial

Abstract: (Abstracted from JAMA 2018;320:43–52) There are only limited data in North American populations on the relative diagnostic effectiveness of cervical cancer screening with primary human papillomavirus (HPV) testing alone compared with cytology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
72
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 50 publications
(77 citation statements)
references
References 0 publications
2
72
1
2
Order By: Relevance
“…The HPV FOCAL RCT [16][17][18] (ISRCTN79347302) compared HPV (Hybrid Capture ® 2 High-Risk HPV DNA Test ® [HC2]; Qiagen Inc., Germantown, MD, USA) (Intervention and Safety [HPV] Arms) versus LBC screening (Control Arm) in women aged 25-65. HC2 positive (HC2+) women in the HPV Arms were triaged by LBC, with immediate colposcopy referral for abnormal cytological findings.…”
Section: Hpv Focal Trial Designmentioning
confidence: 99%
“…The HPV FOCAL RCT [16][17][18] (ISRCTN79347302) compared HPV (Hybrid Capture ® 2 High-Risk HPV DNA Test ® [HC2]; Qiagen Inc., Germantown, MD, USA) (Intervention and Safety [HPV] Arms) versus LBC screening (Control Arm) in women aged 25-65. HC2 positive (HC2+) women in the HPV Arms were triaged by LBC, with immediate colposcopy referral for abnormal cytological findings.…”
Section: Hpv Focal Trial Designmentioning
confidence: 99%
“…5,7,8,24 Randomized trials have demonstrated that screening which includes primary HPV testing is superior to those based on cytology alone, 9,[11][12][13][14]25 including the study from which the sample used in this article was drawn. 15 Studies from large insured populations in the US have come to similar conclusions. 26,27 However, the magnitude of the difference in CIN3+ prevalence at exit screening between the two arms seen in this HPV FOCAL PPE analysis is nonsignificant.…”
Section: Discussionmentioning
confidence: 78%
“…7,8 Comparison of HPV vs. cytology screening in randomized trials has resulted in considerable evidence supporting the use of HPV-based screening for increased detection of CIN2+ at initial screening rounds and reduced subsequent development of cervical cancer and its precursors. [9][10][11][12][13][14][15] Replacement of cytology with HPV-based screening requires reconsidering screening intervals, ages eligible and triage testing to optimize the balance between benefits and harms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Population screening for women for cervical cancer historically has been accomplished by cytology (Papanicolaou test), but multiple clinical trials have provided evidence of improved sensitivity of hrHPV testing for detection of cervical cancer precursor lesions compared to cytology alone over multiple rounds of screening and follow-up. [9][10][11][12][13] The HPV types included in the screening assays are based on epidemiological prevalence data that balance sensitivity and specificity so as not to overtriage women to secondary screening such as colposcopy, and they currently include at most the 14 hrHPV types. Exclusion of less prevalent types from HPV screening reduces possible iatrogenic morbidity from subsequent colposcopy and excisional procedures following detection of viral types of uncertain pathological significance, and also reduces the costs involved in more extensive testing.…”
Section: Introductionmentioning
confidence: 99%